ANTHROPOGENIC APPELLATIVE DERIVED ORONYMS OF HISTORICAL UMAN REGION - Oksana B. Kolesnyk; Svitlana P. Karychkovska (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The aim of the article is to find out the motives for the nomination of some oronyms of the historical Uman region that covers certain districts of Cherkasy, Kirovohrad and Vinnytsia regions and tends to belong to Uman. It is important to analyze the names in the diachronic aspect (their usage from the first mentions in written texts to the present day). The study of onym material involves the use of scientific cognition methods, including descriptive one for sorting out oronyms taken from written texts of the seventeenth and nineteenth centuries and documents from Ukrainian archival institutions, comparative-historical – to establish the reasons for the nomination of land forms recorded in Uman region in the seventeenth century, diachronic – as a means of studying names in historical development. For the first time the oronymic factual material of Uman region of the 17th–19th centuries was introduced into scientific circulation and its structural word-forming and lexical-semantic features in the diachronic aspect are investigated. Given that such objects were renamed, oronyms usually had several variants, and even within the same document, different models of the name of a particular object were recorded. The names associated with the relief elements reflect the landscape diversity of the historical Uman region. The location in Central Ukraine contributed to the creation of an original natural complex of the study area. In proper names, this is expressed primarily in the use of geographical terminology. For the historical Uman region, the terms that have become proper names are beam, valley, grotto, levada, grave, and ravine. The transformation and transition of geographical nouns into microtoponyms take place on the basis of fixing the singularity and individuality of reality itself. But along with the onymization of the toponymic appellation in the microtoponymformation complex constructions have been involved, in the attributive part of which there are lexemes expressed in landscape terminology: Deep Valley; Thunder, or Lion's Grotto; Bloody ravine; The field of the industrious Yurentokh Kushnir. Most names for landforms contain a description of the physical and geographical properties of natural realities. Microtoponyms characterize the objects by their size, shape, and length. The appellative derived names of the historical Uman region which reflect the relief and landscape features of the area are divided into two groups: 1. Microtoponyms of naturogenic origin (reflect lowland terrain, elevated terrain, plain terrain, physical and geographical properties of the object (shape, size and other features of the denotation), indicate the metaphor, flora and fauna of the region); 2. Microtoponyms of anthropogenic origin (related to human activity). It was found that the studied names associated with the elements of relief, reflect not only the diversity of the landscape of the historical Uman region, but also indicate the occupation of the population, ethnic composition; related to the names of structures, buildings, facilities, roads and certain events and occasions. Most of them exist today only in scientific works, having disappeared from the speech of the locals, and some onyms have undergone partial linguistic and component changes during the history of their usage.